Histochemistry of Placental Lipids in Preeclampsia - Prashant Shevade, Dr. Sapna; Arole, Dr. Vasanti; Kishore Bharambe, Dr. Vaishaly (International Journal of Innovative Research in Medical Science, 2016)
Introduction: Physiologic pregnancy is associated with broad spectrum of metabolic adaptations which includes increased lipid metabolism and lipoproteins. Elevated lipid levels in first to third trimester may serve as energy store to fulfil maternal and fetal metabolic needs. Lipids are the major structural components of cell membrane thus are involved in cell replication. Changes in lipid metabolism in pregnancy ensure a continuous supply of nutrients to the growing fetus. Preeclampsia is a systemic disorder which affects 5 to 7 percent of women worldwide and is a major cause for maternal and neonatal morbidity and mortality. Altered placental lipid metabolism in preeclampsia could be a source of placental pathological changes in preeclampsia. The purpose of this study is to find out the exact histochemical localization of lipids in preeclamptic placentae and its correlation with growth and development of the fetus. Methods: 50 normal and 50 preeclamptic placentae were collected immediately after delivery from Department of Obstetrics and Gynecology. Placentae were obtained from known preeclamptic consenting cases who had no history of hypertension before pregnancy or during first 20 weeks of gestation, who had consistently recorded systolic and diastolic blood pressure of 140 / 90 mm of Hg or above and proteinuria ≥ 300mg / 24 hrs. Placental lipid distribution was demonstrated by using Sudan black stain. Results: Fat distribution was more widespread in preeclamptic placentae as compared to normotensive placentae. Conclusion: Abnormal lipid metabolism may be involved in pathogenesis of preeclampsia. Altered lipid profile in preeclampsia can reduce membrane fluidity and disrupt transport across placental trophoblast. This could compromise the transport of nutrients to the fetus.